Phenology and reproductive biology of the southern rockhopper penguin (Eudyptes chrysocome chrysocome) at Isla Pingüino (Santa Cruz Province, Argentina) - Lera, Melisa; Barrionuevo, Melina; Morgenthaler, Annick; Millones, Ana; Frere, Esteban (Polar Biology)
An essential trait in the life history of any animal species is reproduction, including parental care. In seabirds, these actions are well defined and stereotyped. Our study focused on analyzing the parental care behavior, reproductive success, and phenology of the southern rockhopper penguin (Eudyptes chrysocome chrysocome) population of Isla Pingüino, Argentina, through the use of autonomous time-lapse cameras combined with marking of individuals. We compared our results to data obtained from traditional monitoring methods used in the same colony. The phenology of their breeding cycle was the same as in other colonies of the SW Atlantic region. Although parents shared their chick rearing duties, females invested more time in incubating the eggs, while males were more dedicated to chick guarding. Chicks were more frequently fed by females, and males contributed only during the crèche period. The effect of heat stress on chick survival was assessed, since uncommonly high air temperatures were reached during the study, causing unprecedented chick mass mortality. Temperatures of > 25° C were a lethal threshold for chicks; hence, the occurrence of several extremely hot days increased chick mortality. Our combined methodology was useful to evaluate phenology, parental investment, and the variables that affect reproductive success (for instance, weather conditions). We recommend its use in future comparative and long-term studies at remote rockhopper penguin colonies to help improve the quality of monitoring and detect potential threats of this vulnerable species. Fil: Lera, Melisa. Universidad Nacional de la Patagonia Austral. Unidad Académica Caleta Olivia. Centro de Investigaciones Puerto Deseado; Argentina Fil: Barrionuevo, Melina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de ...